2008
DOI: 10.1007/s00417-008-0930-4
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset macular holes following ruptured retinal arterial macroaneurysms

Abstract: Early-onset macular hole formation secondary to a ruptured retinal arterial macroaneurysm occurs mechanically due to the proximity between the macroaneurysm and the fovea. Current and previous reports have suggested that any VA improvement was likely to be limited, at least in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Several macular pathologies have been reported that may develop secondary MH such as cystoid macular edema, subretinal fluid due to rhegmatogenous retinal detachment, and SMH [2][3][4][5][6][7][8][9][10]. In most of the secondary MH associated with SMH, the SMH was caused by rupture of a retinal arterial macroaneurysm (RAM) [17][18][19]. There are several reports of secondary MH associated with choroidal neovascularization, but they developed after absorption of submacular fluid, not SMH [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several macular pathologies have been reported that may develop secondary MH such as cystoid macular edema, subretinal fluid due to rhegmatogenous retinal detachment, and SMH [2][3][4][5][6][7][8][9][10]. In most of the secondary MH associated with SMH, the SMH was caused by rupture of a retinal arterial macroaneurysm (RAM) [17][18][19]. There are several reports of secondary MH associated with choroidal neovascularization, but they developed after absorption of submacular fluid, not SMH [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In a case of SMH due to RAM, it was considered that secondary MH was caused by rapid increase in intraretinal pressure (early onset) or by retinal degeneration (late onset) [18]. Sagara et al reported that the presence of subretinal and sub-internal limiting membrane (ILM) hemorrhages after rupture of a RAM might contribute to formation of an MH [17].…”
Section: Discussionmentioning
confidence: 99%
“…It was perhaps for this reason that 1 month after surgery, the edge of the MH reattached to the retinal pigment epithelium and the MH became smaller. After MH become smaller, ILM peeling induces glial cell proliferation across the hole [17] and small macular defects, may allow easy migration of glial cells. [16] These mechanisms may help the delayed closure occurred in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhages from a macroaneurysm can be located in the vitreous cavity and any of the retinal layers: preretinal hemorrhages, sub-internal limiting membrane (sub-ILM) hemorrhages, intraretinal hemorrhages, and subretinal hemorrhages. A ruptured RAM may rarely leads to macular hole (MH) formation [1][2][3]. MH formation secondary to a ruptured macroaneurysm may occur due to mechanical damage caused by expulsion of blood from the vessels, and the distance of the RAM from the fovea is known to be strongly related to MH occurrence [1,2].…”
Section: Macular Hole Formation Following Vitrectomy For Ruptured Retinal Arterial Macroaneurysmmentioning
confidence: 99%
“…A ruptured RAM may rarely leads to macular hole (MH) formation [1][2][3]. MH formation secondary to a ruptured macroaneurysm may occur due to mechanical damage caused by expulsion of blood from the vessels, and the distance of the RAM from the fovea is known to be strongly related to MH occurrence [1,2]. No previous studies on the occurrence of MH after pars plana vitrectomy (PPV) for a ruptured RAM have been reported.…”
Section: Macular Hole Formation Following Vitrectomy For Ruptured Retinal Arterial Macroaneurysmmentioning
confidence: 99%